Supporting doctor-patient communication: Providing a question prompt list and audio recording of the consultation as communication aids to outpatients in a cancer clinic. Issue 9 (September 2018) - Amundsen, Anita; Bergvik, Svein; Butow, Phyllis; Tattersall, Martin H.N.; Sørlie, Tore; Nordøy, Tone
Highlights: The question prompt list did not increase total amount of question asked. Question prompt list increased questions about prognosis, disease and treatment quality. The question prompt list did not affect physician SDM behavior. Neither question prompt list nor consultation audio record affected patient outcomes. Both communication aids were well received by the patients. Abstract: Objective: To document the effect of a cancer specific question prompt list (QPL) on patients question asking and shared decision-making (SDM), and to evaluate the combined effect of the QPL and consultation audio recording (CAR) on patient outcomes. Method: This exploratory study compared two groups of patients receiving either a QPL or combined QPL/CAR, to a control group. Measurements included number/types of questions asked, and physician SDM behavior (OPTION score). Questionnaire data included anxiety/depression and quality of life (QoL). Results: A total of 93 patients participated (31 Control, 30 QPL and 32 Combined). Patients in the intervention groups asked more questions concerning prognosis (p < .0001), the disease (p = .006) and quality of treatment (p < .001) than patients in the control group, but no impact was found on the OPTION score. An increase in mean consultation length was observed in the intervention groups compared to the control group (44 vs. 36 min; p = .028). Patients rated both interventions positively. Conclusion: Provision of the QPL facilitates patients to ask a broader range of questions, but does not increase physician SDM behavior. Practical implementation: The combination of QPL and CAR seems feasible and should be tested in an implementation study following the disease trajectory.